Trabajo colaborativo como estrategia de aprendizaje en el rea de Matemtica de Educacin Secundaria - Cabanillas Lingan, Narcizo (2021)
The main purpose of this Professional Sufficiency work is to propose the application of collaborative work, as a learning strategy in the area of mathematics, of rural students, awakening the interest and inclination for the study of mathematics and the importance it has in professional pedagogical practice In the theoretical livelihood, the definitions, concepts and theories that support and explain the importance of collaborative work in learning the area of mathematics as an interactive strategy are exposed, allowing the student to develop knowledge, skills and attitudes. Also, in pedagogical sustenture, it deals with the foundation of the area of mathematics, the focus of the area, competencies, skills, and resources to use the student's egress profile when completing basic education, the role of the teacher and the student in the classroom, the pedagogical and didactic processes, culminating in the conclusions and annexes.